Life After SIRI—Where Next?. Issue 5 (October 2019) - Scott, E Marian; Naysmith, Philip; Cook, Gordon
ABSTRACT: Radiocarbon ( 14 C) dating is routinely used, yet occasionally, issues still arise surrounding laboratory offsets, and unexpected and unexplained variability. Quality assurance and quality control have long been recognized as important in addressing the two issues of comparability (or bias, accuracy) and uncertainty or variability (or precision) of measurements both within and between laboratories (Long and Kalin 1990 ). The 14 C community and the wider user communities have supported interlaboratory comparisons as one of several strands to ensure the quality of measurements (Scott et al. 2018 ). The nature of the intercomparisons has evolved as the laboratory characteristics have changed s. The next intercomparison is currently being planned to take place in 2019–2020. The focus of our work in designing intercomparisons is to (1) assist laboratories by contributing to their QA/QC processes, (2) supplement and enhance our suite of reference materials that are available to laboratories, (3) provide consensus 14 C values with associated (small) uncertainties for performance checking, and (4) provide estimates of laboratory offsets and error multipliers which can inform subsequent modeling and laboratory improvements.